The Tapestried Chamber, and Death of the Laird's Jock - Scott, Walter, 1771-1832 (Salt Lake City, UT : Project Gutenberg, 1999)
"The Tapestried Chamber, and Death of the Laird's Jock" by Walter Scott is a collection of two short stories published in 1828. In "The Tapestried Chamber," a distinguished general accepts an invitation to stay at an old castle, only to endure a terrifying nocturnal encounter that leaves him unnerved and desperate to flee. In "Death of the Laird's Jock," an aging Scottish warrior, famed for his prowess with a legendary two-handed sword, must pass his weapon to his son for one final border combat. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_Keepsake_Stories
Waverley novel
Release date is 1999-03-01
Produced by An Anonymous Volunteer, and David Widger
Keywords: Ghost stories; Scotland -- Social life and customs -- Fiction